Pengaruh Pemberian Kredit Terhadap Pendapatan Usah Kecil Dan Menengah Di Koperasi Simpan Pinjam Pintu Air Cabang Lekebai - Oktavia Maria Sa; Henrikus Herdi; Pipiet Niken Aurelia (BADAN PENERBIT STIEPARI PRESS, 2023)
This research was conducted with the aim of examining the effect of granting credit on the income of small and medium enterprises in the Lekebai branch of the Lekebai Savings and Loans Cooperative. In this study, the total population taken was 90 people and for sampling using the slovin formula, the number of samples taken was 45 people. The research method used is a quantitative method. Data collection techniques used are interviews, questionnaires, documentation. While the data analysis used is data quality test, normality test, simple linear regressive analysis, hypothesis testing (t test), coefficient of determination test, heteroscedasticity test, the analytical tool used is IBM SPSS statistic V.26. Based on the results of the study, it was obtained that the provision of credit to the income of small and medium enterprises through the t test with the value obtained from the value of t count <t table, then Ho is accepted and Ha is rejected and it can be concluded that granting credit has no effect on the income of small and medium enterprises.